Deliberative Mini-publics as a Response to the Crisis of Representative Democracy: First Attempts at Institutionalization in European Cities - Podgórska-Rykała, Joanna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The growing crisis of representative democracy and associated citizen dissatisfaction has stimulated innovative thinking about democracy. Over the past two decades, a wide range of democratic innovations have emerged to increase the involvement of ordinary people in politics, combining direct mass participation with in-depth dialogue on pressing public policy issues. The innovations are rapidly spreading territorially, becoming increasingly institutionalised and tailored to specific political, cultural and social contexts. Mini-publics, which are forums for small-scale debate, are particularly remarkable. Faced with citizens’ dissatisfaction with the practice of the public sphere, there are attempts to institutionalise one-off deliberative forums and make them part of a broader political system. This challenge was first taken up by the German-speaking community of Belgium (Ostelbelgien) and followed by other public authorities. Attempts to incorporate mini-publics into the decision-making space have also been made by local authorities – Paris, Newham and Aachen. In this article I argue that citizens’ assemblies are the most advanced method of institutionalising deliberative democracy. I demonstrate that although the first citizen assemblies realised in the world were one-offs, following their example, particularly because of the success of the unique Ostelbelgien model, subsequent public authorities have begun to see this innovation as an opportunity to permanently (rather than just one-off) power democracy and make it more resilient to crises. I also show that local authorities can play a leading role in strengthening and institutionalising deliberative processes using mini-publics. Rosnący kryzys demokracji przedstawicielskiej i związane z nim niezadowolenie obywateli pobudziło innowacyjne myślenie o demokracji. W ciągu ostatnich dwóch dekad pojawił się szeroki wachlarz demokratycznych innowacji, które mają na celu zwiększenie zaangażowania „zwykłych ludzi” w politykę, łącząc bezpośrednie masowe uczestnictwo z pogłębionym dialogiem na temat pilnych kwestii polityki publicznej. Innowacje szybko rozprzestrzeniają się terytorialnie, stają się coraz bardziej zinstytucjonalizowane i dostosowane do konkretnych kontekstów politycznych, kulturowych i społecznych. Na uwagę zasługują szczególnie mini-publiki, będące forami debaty na małą skalę. W obliczu niezadowolenia obywateli z praktyki funkcjonowania sfery publicznej pojawiają się próby instytucjonalizacji jednorazowych forów deliberatywnych i uczynienia ich częścią szerszego systemu politycznego. Wyzwanie to podjęła najpierw niemieckojęzyczna wspólnota Belgii (Ostelbelgien), a za nią poszły inne władze publiczne. Próby włączenia w przestrzeń decyzyjną mini-publik podjęły też władze lokalne – Paryża, Newham i Akwizgranu. W artykule twierdzę, że panele obywatelskie są najbardziej zaawansowaną metodą instytucjonalizacji demokracji deliberatywnej. Dowodzę, że choć pierwsze zrealizowane na świecie panele obywatelskie były jednorazowe, to za ich przykładem, szczególnie za przyczyną sukcesu unikalnego modelu Ostelbelgien, kolejne władze publiczne zaczęły postrzegać tę innowację jako szansę na stałe (a nie tylko jednorazowe) zasilenie demokracji i uczynienie jej bardziej odporną na kryzysy. Wykazuję też, że władze lokalne mogą odgrywać wiodącą rolę we wzmacnianiu i instytucjonalizacji procesów deliberatywnych z wykorzystaniem mini-publik.
Deliberatywne mini-publiki jako odpowiedź na kryzys demokracji przedstawicielskiej: pierwsze próby instytucjonalizacji w europejskich miastach
Keywords: Democratic innovations; deliberative mini-publics; citizens’ assemblies; local government; innowacje demokratyczne; deliberatywne mini-publiki; panele obywatelskie; samorząd lokalny